Decolourisation of textile effluent by using natural adsorbents / Diyana Shazlizashah Azizishah - Azizishah, Diyana Shazlizashah (2014)
The control of water pollution has become of increasing importance in recent years. The release of dyes into the environment constitutes only a small proportion of water pollution, but dyes are visible even in small quantities. Currently, decolourisation of textile effluent is by physio-chemical means, such methods are often very costly and although the dyes are removed, accumulation of concentrated sludge creates a disposal problem. There is a need to find alternative treatments that are effective in removing dyes from large volumes of effluents and are low in cost, such as biological or combination systems. Adsorption technique is widely used to remove certain classes of pollutants from waters, especially those which are not easily biodegradable. Currently, a combination of biological treatment and adsorption on activated carbon is becoming more common for removal dyes from textile effluent. Although commercial activated carbon is a preferred adsorbent for colour removal, its widespread use is restricted due to its relatively high cost which led to the study on alternative non-conventional and low-cost adsorbents. In this study, the use of non-conventional low-cost natural adsorbents to decolourise the simulated dye effluent has been reviewed. Betel nut husk (buah pinang), roasted sunflowers seed husk (kulit kuaci) and pine nuts, are natural adsorbent waste abundantly available in Malaysia were used for the decolourisation of textile effluent. The effects of type of dyes and pH value were studied. The results indicate that betel nut husk and sunflower husk used in this study are an attractive alternative for decolourisation of textile effluent according to their efficiency of the adsorbents to decolourise the simulated dye effluent. The decolourisation worked by using 1.5g of adsorbent at pH 10 for both dyes.